Successful endovascular treatment of ruptured giant aneurysm of arteria lusoria - Pyra, Krzysztof; Szmygin, Maciej; Sojka, Michał; Jargiello, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
An aberrant right subclavian artery (ARSA – arteria lusoria) is one of the most common congenital anomalies of the aortic arch. The majority of patients remain asymptomatic and the findings are incidental [1]. However, depending on the location and the course of ARSA, degree of compression of mediastinal organs and concomitant vascular anomalies it may manifest with dyspnea, dysphagia or chronic cough. We present a patient with ruptured aneurysmal ARSA managed by endovascular means.